Gränsland - Paulsson, Emma (2007)
I have investigated the interaction between man and environment, between my inner reality and a physical place, using a camera as my primary tool. What conceptions do I have and how do they affect how I relate to the outer world? I am not a passive receiver of the surrounding world. Instead I actively (but usually unconsciously) choose what to take in and how I experience it.